2022
DOI: 10.1093/advances/nmab134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protein Quality in Humans and Insights on Stable Isotope Approaches to Measure Digestibility – A Review

Abstract: The recent Food and Agricultural Organization/World Health Organization/United Nations University expert consultations on protein requirements and quality have emphasized the need for the new Digestible Indispensable Amino Acid Score (DIAAS), as a measure of protein quality. This requires human measurements of the true ileal digestibility of individual indispensable amino acids (IAA) until the end of the small intestine. Digestibility is measured using standard oro-ileal balance methods, which can only be achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 102 publications
0
20
0
Order By: Relevance
“…On the other hand, antinutritional factors such as trypsin inhibitors, tannins, and lectins, present in some protein-rich foods such as soybean meal, peas, and beans, could increase protein losses in the terminal ileum, reducing protein hydrolysis and the absorption of amino acids. A more precise determination is proposed taking into account ileal digestibility [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, antinutritional factors such as trypsin inhibitors, tannins, and lectins, present in some protein-rich foods such as soybean meal, peas, and beans, could increase protein losses in the terminal ileum, reducing protein hydrolysis and the absorption of amino acids. A more precise determination is proposed taking into account ileal digestibility [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this measure has been used for twenty years and has been very useful, its limitations have been recognized and should be reassessed. WHO/FAO recommends that amino acids in the diet be considered as individual nutrients, as PDCAAS could underestimate quality [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall mean true ileal digestibility of AAs was 0.92 compared with 0.95 for WPI and 0.63 compared with 0.60 for zein [Calvez et al (17) and data reported in this article]. Both nasoileal intubation and the use of ileostomates to determine true ileal AA digestibility rely on assumptions (6). They are, however, the only 2 models available to directly determine true ileal AA digestibility in the human.…”
Section: Discussionmentioning
confidence: 96%
“…Less invasive indirect methods to determine AA digestibility or availability in humans, such as the dual-isotope method (4) and indicator AA oxidation (IAAO) method (5), are also options. However, these methods, although showing much promise, cannot be considered routine methods and either are still under development or have not been fully validated (3,6). With the IAAO method, relatively costly intrinsic labeling of the food is not required, which is the case for the dualisotope approach, but AA availability observations are limited to one AA per assay period, which requires multiple testing days.…”
Section: Introductionmentioning
confidence: 99%